Project design for surgical department reorganization at hospital-university of Parma - Ferrari, Antonio; Manotti, Pietro; Del Rio, Paolo; Balestrino, Antonio; Fabi, Massimo (Acta Biomedica Atenei Parmensis, 2018)
The article explains the main technical and methodological references of the reorganization of the main surgical activities (for production volumes and case mixes) of the Parma University Hospital. In defining the organizational design we considered the compliance with national laws and regional guidelines, the vision of the Public Enterprise Strategic Management, the attempt to bring the continuity of care through hospital paths, the valorization of the high technical specialty of a hub university center, the recognition of the ability and vocations of Professionals and the search for efficiency of a complex public production system. The project has also responded to the need to pursue greater production efficiency by the entire local health system of Parma, optimizing, at the same time, training courses for Medical Students and Health Professions of the University of Parma transversely with respect to surgical clinical pathways and clinical research.